2014
DOI: 10.1186/1746-4269-10-45
|View full text |Cite
|
Sign up to set email alerts
|

“I eat the manofê so it is not forgotten”: local perceptions and consumption of native wild edible plants from seasonal dry forests in Brazil

Abstract: BackgroundThere is little information available on the factors influencing people’s selection of wild plants for consumption. Studies suggest a suitable method of understanding the selection of edible plants is to assess people’s perceptions of these resources. The use and knowledge of wild resources is disappearing, as is the opportunity to use them. This study analyzes people’s perceptions of native wild edible plants in a rural Caatinga (seasonal dry forest) community in Northeast Brazil and the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 34 publications
2
34
0
13
Order By: Relevance
“…The association between wild edible plants consumption and the belief that it is “food for the poor” was also recently discussed [12,47]. According to the authors, the association with poverty (cultural acceptance) is one of the limiting factors on edible wild plants consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The association between wild edible plants consumption and the belief that it is “food for the poor” was also recently discussed [12,47]. According to the authors, the association with poverty (cultural acceptance) is one of the limiting factors on edible wild plants consumption.…”
Section: Discussionmentioning
confidence: 99%
“…A positive association between age and traditional ethnobotanical knowledge can be expected (Cruz et al 2014, Lepofsky 2009). People from Aldeia reported the importance of some community elders for the valorization of plant knowledge, and we observed a higher proportion of elders in this community, when compared with the other two.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys from Brazilian dry forest (Cruz et al 2014;Nascimento et al 2012 The last five years have been quite prolific in terms of wild food species research within the different Asian regions, providing interesting and significant information about species, distribution, and availability, as well as plant uses and knowledge (Boesi 2014;Ghorbani et al 2012;Hong et al 2015;Ju et al 2013;Kang et al 2012Kang et al , 2013Kang et al , 2014Li et al 2015;Panda 2014;Uprety et al 2012).…”
Section: Americasmentioning
confidence: 99%
“…• Cruz et al (2014), through 12 species in a rural area of the Caatinga, Brazil, evaluated people's perceptions regarding the use of wild edible plants and found that cultural acceptance, flavor, and emergency food were significantly associated with consumption.…”
Section: Culturally Significant Wild Edible Plantsmentioning
confidence: 99%